Routledge Handbook of White-Collar and Corporate Crime in Europe - Erp, Judith Gabriël van (EBL-Schweitzer, 2015)
The study of white-collar crime remains a central concern for criminologists around the world and research concentrates on its nature, prevalence, causes and responses. However, most books on white-collar crime tend to focus on Anglo-American examples, which is surprising given the amount of rich data and research taking place in mainland Europe. This new handbook seeks to reset the balance and, for the first time, presents an overview of state-of-the-art research on white-collar crime in Europe.Adding to the existing Anglo-American body of knowledge, the Handbook will discuss specific Europea